Feasibility of Implementing Disability Inclusive Evidence-Based Health Promotion. Issue 1 (January 2023) - Herman, Cassandra; Eisenberg, Yochai; Vanderbom, Kerri; Tempio, Dori; Gardner, Jevettra; Rimmer, James
Abstract : People with disabilities face a number of barriers to accessing and participating in evidence-based health promotion programs offered within the community. To address these barriers, the program implementation process needs to integrate disability inclusion throughout planning and implementation. The National Center on Health, Physical Activity and Disability's inclusive Community Implementation Process (NiCIP) provides a framework for implementers to systematically integrate strategies into their health promotion programs that increase inclusion while maintaining the fidelity the program. The NiCIP is a community-engaged process that brings key stakeholders together to guide the selection and implementation of data-driven solutions that promote inclusion in, and access to, health promotion programs. In this article, we first provide an overview of the NiCIP. Then, we present a case study exploring one community's experience using the NiCIP to implement a disability inclusive nutrition program within their community.